Twenty-First-Century popular fiction - Murphy, Bernice M. 1977-; Matterson, Stephen (Edinburgh University Press, 2018)
Cover -- Title page -- Contents -- Acknowledgements -- Introduction: 'Changing the Story' - Popular Fiction Today -- Bernice M. Murphy and Stephen Matterson -- 1. Larry McMurtry's Vanishing Breeds -- Stephen Matterson -- 2. 'Time to Open the Door': Stephen King's Legacy -- Rebecca Janicker -- 3. Terry Pratchett: Mostly Human -- Jim Shanahan -- 4. From Westeros to HBO: George R. R. Martin and the Mainstreaming of Fantasy -- Gerard Hynes -- 5. Nora Roberts: The Power of Love -- Jarlath Killeen -- 6. The King of Stories: Neil Gaiman's Twenty-First-Century Fiction -- Tara Prescott -- 7. Jo Nesbø: Murder in the Folkhemmet -- Clare Clarke -- 8. 'It's a Trap! Don't Turn the Page': Metafiction and the Multiverse in the Comics of Grant Morrison -- Kate Roddy -- 9. Panoptic and Synoptic Surveillance in Suzanne Collins's Hunger Games Series -- Keith O'Sullivan -- 10. E. L. James and the Fifty Shades Phenomenon -- Dara Downey -- 11. Fact, Fiction, Fabrication: The Popular Appeal of Dan Brown's Global Bestsellers -- Ian Kinane -- 12. 'I Need to Disillusion You': J. K. Rowling and Twenty-First-Century Young Adult Fantasy -- Kate Harvey -- 13. Jodi Picoult: Good Grief -- Clare Hayes-Brady -- 14. 'We Will Have a Happy Marriage If It Kills Him': Gillian Flynn and the Rise of Domestic Noir -- Bernice M. Murphy -- 15. 'The Bastard Zone': China Miéville, Perdido Street Station and the New Weird -- Kirsten Tranter -- 16. Sparkly Vampires and Shimmering Aliens: The Paranormal Romance of Stephenie Meyer -- Hannah Priest -- 17. 'We Needed to Get a Lot of White Collars Dirty': Apocalypse as Opportunity in Max Brooks's World War Z (2006) -- Bernice M. Murphy -- 18. Genre and Uncertainty in Tana French's Dublin Murder Squad Mysteries -- Brian Cliff -- 19. 'You Get What You Ask For': Hugh Howey, Science Fiction and Authorial Agency -- Stephen Kenneally
Keywords: Geschichte 2000-2017; Unterhaltungsliteratur; Englisch; Aufsatzsammlung